Structural Design for Improving the Strength of Flat Wooden Pallets - Zhu, X; Toyota, H; Ito, D; Doi, K (Journal of physics. Conference series, 2022)
The purpose of this study is to develop a new pallet structure using the inexpensive hinoki wood, which is produced in the Ehime Prefecture, having the same strength as the conventional Oregon pine wood. A new pallet structure was proposed for achieving high-strength by improving the flexural stiffness and compressive stiffness and achieving high-cost performance by using the inexpensive hinoki wood. The results obtained in this study are summarized as follows: deflection of the new type is reduced compared to the standard type, due to the increased bending rigidity of the edge board and deck board; compressive displacement of the new model decreases, as the compressive stiffness of the pallet legs increases; new mold pattern 6 made is higher in strength and rigidity than the standard mold; cost of the new type #6 is 72% of that of the standard type pallet, and cost can be reduced by 28%.